2021
DOI: 10.1123/ijspp.2020-0743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Warm-Up and Sodium Bicarbonate Ingestion on 4-km Cycling Time-Trial Performance

Abstract: Purpose: To examine whether an ecologically valid, intermittent, sprint-based warm-up strategy impacted the ergogenic capacity of individualized sodium bicarbonate (NaHCO3) ingestion on 4-km cycling time-trial (TT) performance. Methods: A total of 8 male cyclists attended 6 laboratory visits for familiarization, determination of time to peak blood bicarbonate, and 4 × 4-km cycling TTs. Experimental beverages were administered doubleblind. Treatments were conducted in a block-randomized, crossover order: interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…The current study findings support previous work on cycling time trials performed in thermoneutral conditions that report ergogenic effects following NaHCO3 ingestion (Gough et al, 2018a(Gough et al, , 2018bGurton et al, 2021a;Hilton et al, 2020). The rise in extracellular acid base balance likely explains the improved performance following NaHCO3 ingestion, as such increases are suggested to increase H + efflux due to the upregulation of the lactate/H + cotransporter, and subsequently more H + is buffered (Marx et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…The current study findings support previous work on cycling time trials performed in thermoneutral conditions that report ergogenic effects following NaHCO3 ingestion (Gough et al, 2018a(Gough et al, , 2018bGurton et al, 2021a;Hilton et al, 2020). The rise in extracellular acid base balance likely explains the improved performance following NaHCO3 ingestion, as such increases are suggested to increase H + efflux due to the upregulation of the lactate/H + cotransporter, and subsequently more H + is buffered (Marx et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…The influence of different warm-up strategies on the ergogenic effects of sodium bicarbonate has been explored in two studies. Gurton et al [207] explored whether an intermittent, sprint-based warm-up relative to lactate threshold (5 min at 50%; 2 min at 60%; 2 min at 80%; 1 min at 100%; 2 min at 50%; and 3 × 10-s maximal sprints with 90-s recovery) impacted the ergogenic effects of individualized sodium bicarbonate ingestion on 4-km cycling time-trial performance compared to a control warm-up (16.5 min cycling at 150 W). Their results showed that the high-intensity warm-up mitigated the ergogenic effects of sodium bicarbonate in club-level cyclists, likely due to the use of the increased buffering capacity during this intense warm-up.…”
Section: Influence Of Warm-up On the Ergogenic Effects Of Sodium Bicarbonatementioning
confidence: 99%
“…The difference between these studies may be related to the time between the warm-up and the exercise bout. Specifically, Gurton et al [207] allowed 10 min between the end of the warm-up and the exercise bout, while Jones et al…”
Section: Influence Of Warm-up On the Ergogenic Effects Of Sodium Bicarbonatementioning
confidence: 99%
“…In addition, our logistic regression did not confirm our own analysis of the mean scores, as only belching showed a significant odds ratio, and that in the opposite direction of our expectations (the odds of reporting belching were higher when drinking water than when drinking milk). Belching is frequently reported during exercise [42][43][44], and it is attributed to oral ingestion of excessive amounts of air [45], which in the present study may have occurred concomitantly with drinking a large volume of water [46]. Resolution of the discrepancies mentioned above regarding fullness, abdominal distension, abdominal pain, and belching may require different protocols; perhaps a more demanding exercise duration and intensity, the explicit prescription of higher fluid volumes, or a combination of both would result in higher symptom scores and frequencies which might provide clearer results.…”
Section: Discussionmentioning
confidence: 99%